2019
DOI: 10.1080/10408444.2019.1605332
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and quality ranking of studies of two phthalate metabolites and anogenital distance, bone health, inflammation, and oxidative stress

Abstract: Phthalates are ubiquitous chemical compounds, and two-di-ethyl phthalate (DEP) and di-isobutyl phthalate (DiBP)-are not currently regulated by the U.S. Congress or the European Union. While many reviews of phthalates have been published, none have examined bone health, inflammation, or oxidative stress; anogenital distance was most recently reviewed in 2014. The objective of this paper is to determine if an association exists between mono-ethyl phthalate (MEP) or mono-isobutyl phthalate (MiBP), metabolites of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 89 publications
(172 reference statements)
0
6
0
Order By: Relevance
“…Phthalate exposure induces osteoporosis through a variety of mechanisms, including estrogen-disruption, PPARγ stimulation, oxidative stress, and inflammation pathways. 15,22,26 30 DEHP exposure also upregulates the gene expressions of IL-8 and IL-10 by zebrafish intestines. 31 Furthermore, a variety of inflammatory cytokines, including plasma IL-6, IL-17A, and tissue TNFα have been shown to be upregulated by DEHP stimulation during the juvenile period in a mouse model through epigenetic regulation.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Phthalate exposure induces osteoporosis through a variety of mechanisms, including estrogen-disruption, PPARγ stimulation, oxidative stress, and inflammation pathways. 15,22,26 30 DEHP exposure also upregulates the gene expressions of IL-8 and IL-10 by zebrafish intestines. 31 Furthermore, a variety of inflammatory cytokines, including plasma IL-6, IL-17A, and tissue TNFα have been shown to be upregulated by DEHP stimulation during the juvenile period in a mouse model through epigenetic regulation.…”
Section: Discussionmentioning
confidence: 96%
“…Phthalate exposure induces osteoporosis through a variety of mechanisms, including estrogen‐disruption, PPARγ stimulation, oxidative stress, and inflammation pathways 15,22,26 . In addition, increased serum C‐reactive protein secondary to DiBP and BBP exposures have been clearly demonstrated in a large‐scale population‐based study 27 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The experimental studies have shown that the main mechanism of osteoporosis under the condition of estrogenic deprivation is the PEs-induced reduction of osteocalcin production [ 99 ]. Impaired synthesis of vitamin D is considered as a second pathogenetic link in the development of osteoporosis caused by PEs exposure, however, information on this problem is controversial [ 47 , 100 , 101 ].…”
Section: Possible Mechanisms Of Endocrine Disruptor Effect On Bone Tissuementioning
confidence: 99%